Public procurement fundamentals lessons from and for the field - Khan, Naushad (Bingley, United Kingdom Emerald Publishing, 2018)
During the last two decades, public procurement evolved in most of the world but is often carried out by government officials with little or no experience with procurement policies and procedures. As a result, substantial amounts of public funds are lost due to wrong selection of suppliers and contractors. While a large amount of literature exists on public procurement, it deals with different aspects such as commercial, environmental, legal, and technical aspects. In this new work, Khan provides an introduction to procurement and efficiency, bringing together these difficult and complex aspects of public procurement in a clear and succinct manner.

From his experience with the World Bank throughout Central and Eastern Europe, Balkans, Caucuses, and Central and South Asia, Khan has created a step-by-step manual for government officials, researchers, and students.
1. What Is Public Procurement: Introduction -- 2. Who Does It and for Whom: Organization and Capacity -- 3. How It Is Done: Procurement Cycle and Procedures -- 4. Contract Management -- 5. How It Is Controlled: Risks to Procurement and Their Mitigation Risks -- 6 New Tools of Public Procurement -- Appendices (A & B) -- Index
Includes index
Keywords: Government purchasing